1981
DOI: 10.1007/bf00428738
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the synthesis of adenylate cyclase in Escherichia coli by the cAMP — cAMP receptor protein complex

Abstract: The synthesis of the adenylate cyclase [ATP pyrophosphatelyase-(cyclizing), E.C. 4.6.1.1.] of Escherichia coli, appears to be regulated negatively by the cAMP receptor protein, CRP. This conclusion is based on a comparison of adenylate cyclase activities measured in vitro with the rates of cAMP synthesis by intact bacteria. The activity of adenylate cyclase, depending on conditions of growth, is also regulated by CRP; this effect, however, is indirect insofar as it is mediated by a protein or proteins under CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Although it is clear that glucose reduces the levels of both CRP and cAMP in wild-type cells, the situation is complicated because CRP and cAMP are mutually regulated. The negative regulation of cAMP level by CRP appears to be particularly important because this regulation is rather strong, as evidenced by the fact that cAMP is overproduced in crpcells (Botsford and Drexler, 1978;Majerfeld et al, 1981). This effect is partly the result of negative regulation of the transcription of cya gene by CRP-cAMP (Aiba, 1985;Mori and Aiba, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is clear that glucose reduces the levels of both CRP and cAMP in wild-type cells, the situation is complicated because CRP and cAMP are mutually regulated. The negative regulation of cAMP level by CRP appears to be particularly important because this regulation is rather strong, as evidenced by the fact that cAMP is overproduced in crpcells (Botsford and Drexler, 1978;Majerfeld et al, 1981). This effect is partly the result of negative regulation of the transcription of cya gene by CRP-cAMP (Aiba, 1985;Mori and Aiba, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…This value is of the same order as the 1,000 to 3,500 dimers assumed to be present in the cell (11,20). A decrease in the level of cAMP is observed in presence of glucose (12,14). Therefore, it seemed interesting to test whether glucose also had an effect on CAP synthesis.…”
mentioning
confidence: 85%
“…cAMP-CRP can act directly by binding within or near promoters of regulated genes to alter the rate of transcription (1,11), or the complex can inhibit the activity of an enzyme, as in the case of adenylate cyclase (cya) (20). cAMP-CRP could also control speA transcription indirectly by controlling the synthesis of a repressor protein or an antisense (divergent) RNA, as in the crp gene (1,28).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown cAMP-CRP regulates the activity of adenylate cyclase (cya) posttranslationally, at the enzyme level (20,41). It appears that the activity of ADC is also indirectly regulated posttranslationally by the cAMP-CRP complex.…”
Section: Discussionmentioning
confidence: 99%